Thor [videorecording (DVD)] - Branagh, Kenneth; Hemsworth, Chris; Portman, Natalie, 1981-; Hopkins, Anthony, 1937-; Hiddleston, Tom; Skarsgård, Stellan; Feore, Colm, 1958-; Stevenson, Ray, 1964-; Elba, Idris; Russo, Rene (Paramount Home Entertainment, 2011)
When the arrogant warrior Thor is banished to Earth from his homeworld of Asgard, he must fight to reclaim his lost powers. Pursued by an invasion force sent to destroy him, the fallen God of Thunder must rise to the battle and learn what it takes to become a true hero.